Optimalisasi Paradigma Informed Consent dari to Disclose Menuju to Understand Sebagai Penghormatan Individual Autonomy - Mohammad Alvi Pratama; Ahnav Bil Aufaq; Rr. Yudiswara Ayu Permatasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The world of health continues to develop, not only focusing on the growth of science, but also relating to the treatment of patients, one of which is informed consent which requires explanation by medical personnel in advance regarding the information needed and enlightens patients so they can consider decisions to be taken rationally. So we need research that aims to determine the achievement of adequate information in the process of informed consent. This research was an analytic descriptive study. The results obtained were dependent on the burden given, namely on the patient's authority. Authority gives patients the right to pull back on optimizing the goals of informed consent. It was found that the knowledge possessed by the patient is closely related to the decision to be determined regarding informed consent. Therefore, the limits of patient knowledge about informed consent also depend entirely on the patient's beliefs and knowledge, so that no matter how optimal the efforts to enlighten knowledge carried out by medical personnel are still unable to measure the depth of knowledge of each patient and of course this is also supported by time constraints. as well as the pace of development of medical science.Keywords: informed consent; paternalism; principle of autonomy ABSTRAK Dunia kesehatan terus berkembang, tidak hanya menitikberatkan pada pertumbuhan ilmu pengetahuan, tetapi juga berkaitan dengan penanganan terhadap pasien yang salah satunya adalah informed consent yang membutuhkan penjelasan oleh tenaga medis terlebih dahulu mengenai informasi yang dibutuhkan dan mencerahkan pasien agar dapat mempertimbangkan keputusan yang akan diambil secara rasional. Maka diperlukan penelitian yang bertujuan untuk mengetahui pencapaian adequate information dalam proses informed consent. Penelitian ini merupakan studi deskriptif analitik. Hasil yang didapat adalah bergantung terhadap beban yang diberikan yakni pada otoritas pasien. Otoritas memberi pasien hak yang dapat menarik ulur optimalisasi tujuan dari informed consent. Ditemukan bahwa pengetahuan yang dimiliki pasien berkaitan erat dengan keputusan yang akan ditentukan berkaitan dengan informed consent. Oleh karena itu, batasan pengetahuan pasien tentang informed consent juga bergantung sepenuhnya kepada keyakinan serta pengetahuan pasien, sehingga seoptimal apapun upaya mencerahkan pengetahuan yang dilakukan oleh tenaga medis masih tidak dapat menakar kedalaman pengetahuan dari masing-masing pasien dan tentu hal tersebut juga didukung oleh keterbatasan waktu serta laju perkembangan ilmu medis.Kata kunci: informed consent; paternalisme; prinsip otonomi